Kemanjuran Intervensi Mindfulness Dalam Mereduksi Perilaku Adiksi Gawai Dan Internet Pada Remaja: Literature Review - Ach. Sudrajad Nurismawan; Hadi Warsito Wiryosutomo; Budi Purwoko (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2023)
Abstract: This study is based on researchers' findings related to the phenomenon of student internet addiction, either directly or indirectly. Therefore, this study intends to examine and apply a mindfulness approach to reducing internet addiction. Through the literature study method, the researcher tries to compile, analyze, and present study materials systematically according to the research objectives. The results of the study of thirteen articles that the researchers analyzed can be said to be the key to mindfulness interventions that are useful in reducing internet addiction, daring games in adolescents, and positively impacting their health. School counselors can learn and practice mindfulness interventions in dealing with students' internet addiction in stages.Keywords: Mindfulness, Addiction, Youth.